The dynamics of willingness to communicate in synchronous Chinese online language teaching and learning : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Applied Linguistics at Massey University, Manawatū, New Zealand - Huang, Huan (Massey University, 2023)
While there has been growing academic attention to researching the dynamics in willingness to communicate (WTC), the variability in learners’ WTC over different timescales has remained relatively under-researched, particularly in online language learning contexts. Although research on the dynamics of WTC has largely drawn from the learners’ perspectives, little attention has been paid to individual learners’ WTC by focusing on the perceptions of both the teachers and the learners. This study was carried out in a one-to-one Chinese language learning videoconferencing setting, where one tutor was partnered with one learner (four pairs in total) undertaking five or ten sessions, each lasting 20 minutes. This Synchronous Chinese Online Language Teaching (SCOLT) project, jointly offered by Beijing Language and Culture University (BLCU) and Massey University (MU), was purposefully built to support adult distance language learners of Chinese in New Zealand in experiencing learner-centred, personalised language learning in online environments. The study aims to explore the unique experience of each learner and to understand their WTC in Chinese (WTCC) across different timescales, including over single interactions, single sessions, and a series of sessions. Taking into account multidimensional factors affecting learners’ WTCC, the tutors’ and learners’ perceptions across different timescales were also examined. Informed by Complex Dynamic System Theory (CDST), this study employed a qualitative longitudinal case study research design. Multiple methods were applied for data collection, including the idiodynamic method, the experience sampling method (ESM), journals, the Session-based WTCC scales, stimulated recalls based on the learning session recordings, and a pre-session questionnaire. In order to portray insights about WTCC within each dyad, this study also conducted the idiodynamic method with the tutors to collect their views about their learners’ WTCC during communicative activities. Findings suggest how learners’ WTCC on multiple timescales fluctuated during Chinese language communication activities. Learners’ WTCC changed and stabilised over time, emerging from their interactions with the tutors, and the online environment. Furthermore, the dynamic and non-linear nature of learners’ WTCC also appeared in micro timescales, such as minutes and seconds, which were influenced by the complex interplay of the individual (learners’ self-perceived communicative competence, negative and positive emotions); the situational (topic-related factors, tutor-related variables, and the multimodality); and learners’ agency to reinforce or resist the impacts of the factors at a specific time. The four learners showed quite different dynamics in WTCC, highlighting the uniqueness of individuals and the inherent complexity of WTCC systems. In addition, tutors’ and learners’ perceptions of learners’ WTCC became more consistent over time with a desire to build and maintain the relationship and to select communication topics convergent with learners’ communication needs. However, the respective ratings did not always match due to the complex and dynamic nature of learners’ WTCC. This study contributes to the literature in the field of learners’ WTC research by extending our understanding of the dynamics of learners’ WTCC in online Chinese language learning context. Based on the findings, this study has implications for research methodology and theoretical frames, shedding light on how learners’ WTCC change at different timescales. Implications for online language learning and teaching are identified which can inform one-to-one contexts, teacher training and future research.
Keywords: Chinese language; Study and teaching (Higher); English speakers; New Zealand; Second language acquisition; Social aspects; 470401 Applied linguistics and educational linguistics